IMPACT ANALYSIS OF THE FUJI LESTARI PROGRAM ON FISH RESOURCE RECOVERY AND THE ADVANCEMENT OF SUSTAINABLE DEVELOPMENT GOAL 14 (LIFE BELOW WATER) IN THE JAVA SEA (FISHERIES MANAGEMENT AREA 712), INDONESIA - Nugraha Hasan, Reza Adhitama; Rahardjo, Oktavian; Bachtiar, Naila Taslimah (Department of Marine Engineering, Universitas Hang Tuah, 2025)
The Fuji Lestari program, implemented regularly by the Ministry of Marine Affairs and Fisheries (KKP) through the Fishing Technology Center (BBPI), aims to restore fishery resources. The Java Sea (FMA-712), characterized by the highest population of fishers, has been categorized as fully exploited, necessitating the Fuji Lestari program to restore its condition. This study evaluates the program's impacts in Bangsring waters, Banyuwangi Regency (2011); Panjang Island, Jepara Regency (2021); and Karang Jeruk, Tegal Regency (2024). The methodology included field observations, underwater visual census (UVC), and interviews using purposive sampling targeting program beneficiaries. Data analysis assessed ecological and economic impacts. Ecological impacts included changes in coral cover in Bangsring and Panjang Island, as well as increases in fish abundance and diversity in Karang Jeruk. Economic impacts were analyzed by calculating the total economic valuation (TEV) for the three locations. Results show a significant increase in live coral cover of 2.4 hectares in Bangsring waters and 1 hectare in Panjang Island waters. In Karang Jeruk, reef-associated fish species increased from 6 to 12 species, with a diversity index rising from 1.49 to 1.71. The TEV from direct, indirect, existence, and option benefits in Bangsring, Banyuwangi Regency was IDR 11,856,378,385; Panjang Island, Jepara Regency was IDR 5,136,896,500; and Karang Jeruk, Tegal Regency was IDR 9,655,638,600. Variations in impact across regions depended on environmental damage levels and the characteristics of fisher beneficiaries. Furthermore, stakeholder collaboration is crucial in optimizing existing opportunities to ensure the program's future success.